Koncepcje ochrony środowiska w cywilistyce Związku Radzieckiego: [Conceptions of the environment protection in the civil law theory in teh Soviet Union] (Studia Prawnicze / The Legal Studies, 1986)
In the Soviet law doctrine in the last years it can be observed the evident increase of interest to problems of the environment protection in the civil law. We can mark out two tendencies in the theoretical analises. The first one, older, includes the problems of damages in the natural objects. The development of the legislation and theoretical analises aims at ensuring the complete compensation and at the same time to relief of the victims situation. This aim can be achieved: first - by extension of the civil liability grounds, especially by acceptation of the liability independently of the guilt; second - by setting up special methods and rates as a base to the calculation of damages. The second tendency, later, includes the problems of the liability for damages caused to persons health as a consequences of the environment pollution. This institution does not work in court practice to-day, but it provokes a great interest in the civil law theory. It is special significant that: first - it was suggested the conception of personal right to a decent environment which can be protected by -civil law means; second - it was made an attempt to enlivening the negatorian claims and to include them in the law system of environment protection.